2016
DOI: 10.5958/2395-6194.2016.00002.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lycopene and Levamisole in Management of Oral Lichen Planus-A Comparative Study

Abstract: Objective: Oral Lichen Planus (OLP) is known to be persistent and resistant to treatment. Corticosteroids are the preferred mode of intervention in OLP, long courses of which have been shown to cause adverse effects. The goal of this study was to compare the safety and efficacy of Lycopene and of Levamisole in the management of Oral Lichen Planus. Methods: 50 symptomatic OLP patients satisfying the inclusion criteria were randomly divided into two groups (A and B). Group A patients were administered lycopene 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…She observed that two (8%) patients had complete remission of lesions (score 4 = 90-100% remission of sign and symptoms), and the remaining patients (n = 23, 92%) had partial remission of lesions. The results of our study were more or less similar to the Pratibha et al [14] study. Similarly, a double-blinded, placebo controlled study was conducted by Saawarn et al, [6] using lycopene at a dose of 8mg/day for 8 consecutive weeks in 15 patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…She observed that two (8%) patients had complete remission of lesions (score 4 = 90-100% remission of sign and symptoms), and the remaining patients (n = 23, 92%) had partial remission of lesions. The results of our study were more or less similar to the Pratibha et al [14] study. Similarly, a double-blinded, placebo controlled study was conducted by Saawarn et al, [6] using lycopene at a dose of 8mg/day for 8 consecutive weeks in 15 patients.…”
Section: Discussionsupporting
confidence: 92%
“…Complete remission of lesions was seen in two (15.5%) patients, while remaining (n = 11, 84.6%) had partial remission of lesions after 8 consecutive weeks of treatment with lycopene. A similar study was conducted by Pratibha et al, [14] who assessed the effect of lycopene 8 mg/day for 8 consecutive weeks in 25 patients using the Tel Aviv San Francisco Scale. She observed that two (8%) patients had complete remission of lesions (score 4 = 90-100% remission of sign and symptoms), and the remaining patients (n = 23, 92%) had partial remission of lesions.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…8 Corticosteroids are the main treatment for OLP, but due to their local (burning sensation and irritation) and systemic (immunosuppression) side effects, various studies have been carried out to find alternative treatments, such as herbal medicines, 9 which have been widely used because they are safe, easy to find and low cost. 10 Thus far, many studies have shown that herbal medicines may reduce the severity of OLP; for example, Liu Wei Di Huang, 9 Tripterygium glycosides, 9 Zeng Sheng Ping, 9 liquorice, 11 purslane, 12 lycopene, 13 raspberry, 14 propolis, 15 green tea, 16 Ignatia amara, 17 aloe vera, 18 quercetin 19 and Curcuma longa. 20 Different types of herbs have had varied results; for example, curcumin may reduce the inflammatory cytokine response caused by the activity of T lymphocytes in OLP.…”
Section: Introductionmentioning
confidence: 99%